2020
DOI: 10.1029/2019jb018034
|View full text |Cite
|
Sign up to set email alerts
|

Present‐Day Vertical Land Motion of Australia From GPS Observations and Geophysical Models

Abstract: The secular rate of Australia's vertical surface deformation due to past ice‐ocean loading changes is not consistent with present vertical velocities observed by a previously sparse network of Global Positioning System (GPS) sites. Current understanding of the Earth's rheology suggests that the expected vertical motion of the crust should be close to zero given that Australia is located in the far field of past ice sheet loading. Recent GPS measurements suggest that the vertical motion of the Australian contin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 105 publications
5
22
0
Order By: Relevance
“…The average uncertainties from our approach at GPS and TG sites were 0.65 and 0.71 mm/yr, respectively, comparable with 0.83 and 0.87 mm/yr inferred from Hector-derived (at GPS) and GPS-Krig (at TG) uncertainties, respectively. The GPS-inferred VLM field showed that the Australian plate is largely subsiding with weighted mean rates of -0.10, -0.38, -0.95 and -0.62 mm/yr in the NW, NE, SW and SE regions, respectively, in general agreement with previous GPS estimates of subsidence (Hammond et al, 2021;Riddell et al, 2020). The estimates at TGs revealed localized VLM trends around the continent that are not completely consistent with the GPS-Krig interpolations.…”
Section: Linear Vlmsupporting
confidence: 78%
See 2 more Smart Citations
“…The average uncertainties from our approach at GPS and TG sites were 0.65 and 0.71 mm/yr, respectively, comparable with 0.83 and 0.87 mm/yr inferred from Hector-derived (at GPS) and GPS-Krig (at TG) uncertainties, respectively. The GPS-inferred VLM field showed that the Australian plate is largely subsiding with weighted mean rates of -0.10, -0.38, -0.95 and -0.62 mm/yr in the NW, NE, SW and SE regions, respectively, in general agreement with previous GPS estimates of subsidence (Hammond et al, 2021;Riddell et al, 2020). The estimates at TGs revealed localized VLM trends around the continent that are not completely consistent with the GPS-Krig interpolations.…”
Section: Linear Vlmsupporting
confidence: 78%
“…GPS observations of VLM across Australia suggest the continent is subsiding overall (Hammond et al, 2021;King et al, 2012;Riddell et al, 2020). Recent work by Riddell et al (2020) using GPS time series showed the widespread pattern of subsidence cannot be fully explained by GIA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gruszczynska et al [ 30 ] used multichannel singular spectrum analysis (MSSA) to model the common seasonal signals in GPS observations in different regions around the world and without influencing the high frequency part of the spectra. Some other data-driven mathematical methods have been proposed to be used in modeling the geophysical signals from regional geodetic time series, e.g., principle component analysis (PCA) and independent component analysis (ICA), which have been widely used in smoothing and modeling GPS time series [ 15 , 23 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. ICA has especially been widely used in the separation of potential sources of seasonal signals in vertical GPS coordinate time series, and the main independent components (ICs) were thought to be consistent with some of the geophysical signals [ 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Continuous GNSS (Global Navigation Satellite System) time series has been extensively used in Earth surface motion monitoring (e. g., plate tectonics [1,2], sea-level variation [3,4], polar research [5] and other [6,7]). Multi-year combination dense GNSS network solutions of the EPN weekly SINEX files [8] play an important role in providing accurate stations' positions and velocities in the European territory.…”
Section: Introductionmentioning
confidence: 99%